Morphologic characterization of specific granules in Greyhound eosinophils - Iazbik, M C (Veterinary clinical pathology, 2005)
BACKGROUND: "Vacuolated" eosinophils (ie, eosinophils with empty, nonstaining granules) have been described previously in normal Greyhounds. However, to our knowledge, detailed studies of granules in vacuolated and normal eosinophils in this breed have not been performed